A comprehensive analysis of the floral transition in ma bamboo (Dendrocalamus latiflorus) reveals the roles of DlFTs involved in flowering. (25th April 2022) - Fan, Huijin; Zhuo, Renying; Wang, Huiyuan; Xu, Jing; Jin, Kangming; Huang, Biyun; Qiao, Guirong
Abstract: Bamboo has a unique flowering characteristics of long and unpredictable vegetative period, which differs from annual herbs and perennial woody plants. In order to understand the molecular regulatory mechanism of bamboo flowering, a comprehensive study was conducted in ma bamboo ( Dendrocalamus latiflorus Munro), including morphological, physiological and transcriptiome analyses. Differentially expressed genes related to the flowering pathway were identified by comparative transcriptome analysis. DlFT1, a homologous gene of FT/Hd3a, was significantly upregulated in flowering bamboo. Direct differentiation of spikelets from calli occurred and the downstream gene AP1 was upregulated in the transgenic bamboo overexpressing DlFT1 . Transgenic rice overexpressing DlFT1 showed a strong early flowering phenotype. DlFT1 and DlTFL1 could interact with DlFD, and DlTFL1 delayed flowering. It is presumed that DlTFL1 plays an antagonistic role with DlFT1 in ma bamboo. In addition, the expression of DlFT1 was regulated by DlCO1, indicating that a CO-FT regulatory module might exist in ma bamboo. These results suggest that DlFT1 is a florigen candidate gene with conservative function in promoting flowering . Interestingly, the results have shown for the first time that DlFT2 can specifically interact with E3 ubiquitin ligase WAV3, while DlFT3 transcripts are mainly nonsense splicing. These findings provide better understanding of the roles of the florigen gene in bamboo and lay a theoretical basis for regulating bamboo flowering in the future.